2017
DOI: 10.3892/br.2017.985
|View full text |Cite
|
Sign up to set email alerts
|

Serum pepsinogen and gastrin-17 as potential biomarkers for pre-malignant lesions in the gastric corpus

Abstract: Abstract. There is a lack of non-invasive screening modalities to diagnose chronic atrophic gastritis (CAG) and intestinal metaplasia (IM). Thus, the aim of the present study was to determine the sensitivity and specificity of serum pepsinogen I (PGI), PGI:II, the PGI:II ratio and gastrin-17 (G-17) in diagnosing CAG and IM, and the correlations between these serum biomarkers and pre-malignant gastric lesions. A cross-sectional study of 72 patients (82% of the calculated sample size) who underwent oesophageal-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
2
16
1
Order By: Relevance
“…Among the family of gastrin, G-17 particularly plays a critical role in the regulation of gastric acid secretion 43 . Some other researches similarly found high level of serum gastrin was associated with precancerous lesions and gastric cancer in Asians [44][45][46][47] . The results of the present study demonstrated that the prevalence of atrophic gastritis tended to increase from benign to malignant lesion.…”
Section: Discussionmentioning
confidence: 85%
“…Among the family of gastrin, G-17 particularly plays a critical role in the regulation of gastric acid secretion 43 . Some other researches similarly found high level of serum gastrin was associated with precancerous lesions and gastric cancer in Asians [44][45][46][47] . The results of the present study demonstrated that the prevalence of atrophic gastritis tended to increase from benign to malignant lesion.…”
Section: Discussionmentioning
confidence: 85%
“…Among these studies, 115 articles were excluded from the final analysis due to the following reasons: narrative review article ( n = 13), letter, comment, editorial or reply to questions ( n = 1), study protocol ( n = 1), incomplete data ( n = 92), and systematic review/meta-analysis or consensus report ( n = 8). The remaining 14 studies [20,21,22,23,24,25,26,27,28,29,30,31,32,33] were included in the quantitative synthesis. Eight studies [20,23,24,27,29,30,31,32] adopted the cut-off standard of PG I ≤70 ng/mL and PG I/PG II ratio ≤3, eight studies [21,22,25,26,27,28,30,33] adopted the cut-off standard of PG I/PG II ratio ≤3, and only two studies [27,33] adopted the cut-off standard of PG I ≤70 ng/mL.…”
Section: Resultsmentioning
confidence: 99%
“…From the 14 studies [20,21,22,23,24,25,26,27,28,29,30,31,32,33] for the diagnosis of CAG, we identified a total of 5541 patients (2220 patients with CAG vs. 3321 patients without CAG). Among them, 11 [20,22,23,24,25,26,27,28,30,31,32] were case-control studies, whereas two [21,33] were cross-sectional studies and only one [29] was cohort study. Seven studies [20,24,28,29,30,31,33] were conducted in Asia, whereas the remaining studies were conducted in Europe [21,22,26,27,32] and South America [23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations